Evaluasi Desain Terminal Penumpang Bandar Udara Sentani Jayapura Provinsi Papua - Samin Samin; Alifia Dian Khoiriani; Alik Ansyori Alamsyah (Borneo Engineering : Jurnal Teknik Sipil, 2021)
Sentani Airport serves public using air transportation with increasing people mobility conditions because Jayapura is the National Activity Center, so it causes frequent accumulation of passengers in the terminal area especially during peak hours. To determine the effectiveness of the terminal in accommodating the flow of passenger movement, it is necessary to evaluate the terminal design of Sentani Airport. The method used is to calculate the number of PWS with passenger distribution patterns, calculate the standard area of terminal capacity using references from SNI 03-7046-2004 and SKEP 77/VI/2005, calculate the terminal LOS with IATA standards, measure the airport service standards based on PM 178 of 2015, processing passengers’ perceptions with IPA and QFD methods and forecasting with simple linier regression. From the analysis, Sentani Airport terminal gives passengers mobility with low service performance value, so it is rated as less optimal. In addition, the limited availability of several facilities causes the passengers feeling less comfortable. Thus, it is necessary to re-design the passenger terminal area and re-management the facilities according to Angkasa Pura standards.